La confrontation du roi, des nobles et des paysans dans La serrana de la Vera de Luis Vélez de Guevara - Hélène Tropé (Etudes Epistémè)
Written in 1613, Vélez de Guevara’s tragedy La serrana de la Vera first looks like one of those numerous Spanish plays about countrymen’s honour. However, this play differs from such a model insofar as its denouement is unconventional : the soldier who raped the mountain girl (called the « serrana ») is killed by the young woman herself, rather than by the community of country people, as is usually the case in those plays. The serrana then runs away into the mountains and becomes a female bandit who kills the men she encounters. The king, far from forgiving the murder of the young nobleman, has her executed. This violent denouement poses the problem of the meaning of such a peculiar play in which the victim is punished. This article proposes then to show how this tragedy illustrates the dangers embodied by this strange androgynous character of a lawless woman, a sort of ogress, whom only the monarch, the manly and civilizing entity, manages to eliminate to restore Law and Order.